Comparison of Students With and Without Problematic Smartphone Use in Light of Attachment Style - Eichenberg, Christiane; Schott, Markus; Schroiff, Athina (Frontiers in Psychiatry, 2019)
Background: Nowadays, media addictions are especially of high relevance to psychotherapeutic practice. More recently, this particularly includes excessive smartphone usage. Even though a growing number of scientific literature and also mainstream media highlight problematic smartphone use as a serious health problem, there is only little research on this issue. Objective: The aim of this study was to examine this phenomenon with a focus on attachment-specific differences between students with and without problematic smartphone use. Method: A survey was carried out on all enrolled students of the Sigmund Freud University Vienna. The Smartphone Addiction Scale (SPAS) was used to differentiate between students with and without problematic smartphone use. The attachment style was assessed using the Bielefeld Partnership Expectations Questionnaire (BFPE). Results: Of the total sample, 75 of the students (15.1%) showed a problematic smartphone use. A positive correlation between excessive smartphone usage and an insecure attachment style was found. Discussion: Therapy for problematic smartphone use should be carried out in light of patient’s attachment style. Further research into other factors of mental stress and personality is needed to better understand problematic smartphone use.